Analisis Kebutuhan Bahan Ajar Mahasiswa pada Mata Kuliah Ekologi Tumbuhan - Muliana GH; A. Farida Arsal (Peneliti.net, 2022)
Learning resources and teaching materials are important components in the lecture process. This research is a qualitative descriptive study. Retrieval of data using observation and questionnaire techniques. The purpose of this study was to describe and analyze the results of the questionnaire on the needs of teaching materials as one of the main learning resources for students. Respondents were 47 students from Makassar State University. The research instrument used a questionnaire for teaching materials for plant ecology courses which were presented via the Google form platform. Data collection was carried out by distributing teaching material needs questionnaires to students who were programming plant ecology courses and to students programming plant ecology courses. The data analysis technique is by describing the results of the questionnaire for the needs of teaching materials for plant ecology courses, which are analyzed in detail. The results of this study are 1) Learning resources used in plant ecology courses generally use the internet, 2) Plant ecology material is difficult to understand, 3) Learning resources needed for plant ecology courses are in the form of modules, 4) Development of modules as eye learning resources plant ecology lectures need to be done. The results of the analysis are expected to be used as a basis for making teaching materials and developing teaching modules in plant ecology courses.